Pengaruh Perceived Organizational Support dan Job Crafting Terhadap Organizational Citizenship Behavior pada Yayasan Masjid Agung Baitunnur Blora - Anggita Ayu Puspitaningrum; Ahmad Sidiq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of the research is to determine the influence of Perceived Organizational Support and Job Crafting on Organizational Citizenship Behavior at the Baitunnur Great Mosque Foundation, Blora. This research method uses a population of employees at the Baitunnur Blora Great Mosque Foundation as research subjects. The number of respondents in this research was 111 as a sample and census as a sampling technique. The data collection method is a questionnaire. This test uses instrument tests, classical assumptions and hypothesis testing. This research found that factors such as Perceived Organizational Support and Job Crafting influence Organizational Citizenship Behavior at the Baitunnur Great Mosque Foundation, Blora.